2022
DOI: 10.1123/jtpe.2021-0230
|View full text |Cite
|
Sign up to set email alerts
|

Achievement Emotions, Intention to Be Physically Active, and Academic Achievement in Physical Education: Gender Differences

Abstract: Purpose: The objective of the study was to evaluate the relationships among the achievement emotions experienced during physical education classes, the intention to be physically active, and academic achievement. Methods: The sample consisted of 764 Spanish secondary education students (348 boys and 416 girls). Results: Pride, enjoyment, and hopelessness were the main emotions to explain the intention to be physically active, whereas enjoyment and boredom were the most important emotions to explain academic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…For these reasons, it may be necessary to explore possible additional sources of PA opportunities, including extracurricular PA participation [ 15 ]. In turn, as the literature has shown [ 16 , 17 , 18 ], positive psychological conditions during PE have been proposed as positive predictors of the intention to engage in physical activity. The intention to be physically active has been widely used in the literature as a predictor of the practice of physical activity [ 19 , 20 , 21 , 22 ], since it is a determinant of active behaviour [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For these reasons, it may be necessary to explore possible additional sources of PA opportunities, including extracurricular PA participation [ 15 ]. In turn, as the literature has shown [ 16 , 17 , 18 ], positive psychological conditions during PE have been proposed as positive predictors of the intention to engage in physical activity. The intention to be physically active has been widely used in the literature as a predictor of the practice of physical activity [ 19 , 20 , 21 , 22 ], since it is a determinant of active behaviour [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are studies in which intention has not been linked to the practice of PA [ 25 ], but rather it has been shown that other complementary constructs are necessary to improve the ability to predict PA [ 26 ]. To satisfy this requirement, other approaches have been proposed to extend the theory by disaggregating motivation [ 27 ] and emotions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations